Personal conscience and the medical profession - Ciccone, Lino (Medicina e Morale, 2024)
When we speak of 'conscience' (implying 'moral'), we are referring to a kind of permanent inner sensitivity to that class of values we call moral, and which ethical norms help us to grasp and promote in various concrete situations. This does not pretend to be a definition of conscience, but merely a telegraphic reminder of the reality that is in question.